PENGARUH LATIHAN LEMPAR SHUTTELCOCK TERHADAP KEMAMPUAN PUKULAN LOB PADA PEMAIN BULUTANGKIS PB BUNGO SPORT KABUPATEN BUNGO - Saputra, Deddy Rahmat (Jurnal Tunas Pendidikan, 2023)
This research started from the existence of several problems including the inaccuracy of choosing models and forms of training in achieving the desired goals and targets, especially increasing the ability of lob shots and the unknown effect of shuttlecock throwing exercises on increasing the ability of lob strokes in PB Bungo Sport Badminton Players in Bungo Regency. This study aims to determine the effect of the shuttlecock throwing exercise on increasing the lob ability of badminton athletes in PB. Bungo Sport Bungo Regency. This type of research is an experiment with the design of "The One Group Pretest-Postest Design". The population in this study were PB badminton athletes. Bungo Sport Bungo Regency, totaling 13 athletes. The sampling technique used purposive sampling, with the following criteria: (1) male and female (2) aged 9-11 years, (3) willing to be a sample. Based on these criteria, 10 athletes met. The instrument used is the lob ability test (French Test). Data analysis used t test with a significance level of 5%. The results showed that there was a significant effect of shuttlecock training on increasing lob hitting ability. In this case, the athlete's lob shot ability who was taught with exercise treatment (posttest) was higher than before the treatment exercise treatment. This is evidenced by the value of Fcount (1,28) < Ftable (2,69). In addition, from the results of hypothesis testing conducted with the t-test, it is known that there is a significant effect after the posttest measurement, which is indicated by the tcount 11,42> ttable 1,78. Therefore, it can be concluded that the treatment has a significant effect on increasing the lob ability of badminton athletes in PB. Bungo Sport Bungo Regency.